Encounters with national stereotypes in foreign language teaching - Stopar, Andrej (ELOPE (Ljubljana), 2015)
Teaching (or learning) a foreign language is a complex, interdisciplinary undertaking. Teachers and students are required to tackle aspects of language that transcend its merely linguistic component. This article discusses the relationship between language, thought and culture, and explores some aspects of the integration of cultural content in the English classroom. To achieve these goals, a study is conducted that identifies the main stereotypes about Americans among Slovenian university students of English as a foreign language. The results of the research can be used as a means of questioning some frequent stereotypes about Americans, and thus contributing to the fulfilment of (sometimes seemingly abstract) curricular aims that emphasize the significance of intercultural communication, awareness of cultural variety, and intercultural sensitivity.
Keywords: medkulturna komunikacija; nacionalni stereotipi; poučevanje kulture; učni načrti